Artificial intelligence : the simplest way - Overton, Jerry (O'Reilly Media, 2018)
Artificial intelligence is quickly moving from experimental to practical use. In the next few years, every business is going to need an AI strategy just to stay competitive. Getting access to AI technology is relatively straightforward; the hard part is applying the technology to a specific business context. This practical ebook guides you through the fundamental AI concepts and explains the simplest way for your organization to get started with this technology. Author Jerry Overton, a data scientist and fellow in DXC's Analytics Group, shows leaders in business, analytics, and IT how to choose an AI method, tie it to a specific business need, and then build, execute, and scale an AI solution to adapt to changing circumstances. You will learn ways to: Determine where AI can be useful in your organization by prioritizing areas that need improvement Create data stories that illustrate how AI can help bring about a solution Choose an AI strategy that produces practical results, using the scientific method as a guide Scale up by building and deploying utility services to make your AI available wherever it's needed Check your solution for bias and other ethical concerns by anticipating the AI's behavior.